A new species of the genus Garra (Teleostei: Cyprinidae) from the Barak River drainage, Manipur, India - Roni, Narengbam; Vishwanath, Waikhom (Zootaxa, 2018)
Garra substrictorostris, a new labeonine species, is described from the Barak River drainage in Manipur, India. It is distinguished from its congeners by the combination of the following characters: a prominent unilobed antrorse proboscis, with 3–5 medium to large multicuspid tubercles on its anterior margin; 4–6 multicuspid tubercles on its anteroventral margin; a prominent transverse lobe with 14–20 multicuspid tubercles; the lateral surface of the snout slightly elevated, lobular with 7–11 small tubercles; 5½ transverse scale rows above the lateral line and 3½ or 4½ scale rows between lateral line and anal-fin origin.